Preanalytical effects on biochemical results for medical decisions in urea cycle defects - Bachmann, Claude (Journal of Pediatric Biochemistry, 2014)
Reliable biochemical results are needed for the diagnosis and follow-up of patients with hyperammonemic disorders. Preanalytical factors influence the results and can lead to erroneous interpretations and medical decisions. I emphasize the need of quality assessment in the laboratory, of adequate time of sampling for ammonia and amino acid analyses after food intake in urea cycle disorders and on the rational estimation whether the intra-individual difference between two sequential results of an analyte is solely due to analytical variance or not. I present arguments for banning capillary blood samples as well as whole blood samples collected on filter paper for confirming or excluding a suspected diagnosis or for controlling data in the follow-up of a disease or its therapy.
Keywords: Urea cycle disorders; preanalytical factors; sampling time; newborn screening